Design and Fabrication of a Roll-Cage of an Electric All Terrain Vehicle - Bawane, Manish; Changde, Chinmay; Kapkar, Sourabh; Soman, Shaunak; Mupidwar, Kartik (Journal of Advance Research in Mechanical and Civil Engineering (ISSN: 2208-2379), 2015)
This Paper aims to design and fabrication of a roll-cage of an electric all terrain vehicle made up of Circular cross section pipes. Modeling and Analysis are performed using Software i.e catia according to the rulebook provided. The maximum deflection is determined by performing static Analysis with consideration to position of motor and battery position , braking System, steering system, seat position and many more. The FEA results are verified by comparing with analytical calculations. Considering these results modal is modified.